Common Winter Illness - A Seasonal Suffering- An Editorial (The Planet, 2021)
As Late-Autumn is preparing to take farewell, winter is coming with its charming weather of foggy mornings and chilly evenings. Winter is the season of fun and celebration. It’s the time to rejoice! It’s the season of endless cups of tea and coffee. It is also that time of the year filled with enjoying holidays, exciting get-togethers, holiday parties and picnic, family dinners and the wedding ceremony.  However, as we welcome and get ready for the charming winters, it is also important that we don’t forget the unpleasant side of the season, such as the fall in temperature and other related factors that can lead to a multitude of health problems, called winter diseases or seasonal diseases.People get sick with changing seasons; the winter season brings a lot of diseases with the onset of low temperatures. Some people such as very young, very old or with a compromised immune system, are more susceptible to catching these common diseases. Some precautions can keep these diseases at bay to get most out of this season.The shift in temperature causes viruses to flourish which then spread diseases. People are indoors more often, allowing viruses to pass more easily from one person to another. And the cold, dry air may weaken resistance. Although these virus diseases may occur throughout the year, common colds, flus, sore throat and other respiratory illnesses such as sinusitis are more common in winter months [1]. Pre-existing respiratory conditions such as COPD or asthma become worse during winter season causing more distress to the patients; winter season becomes miserable to these persons.Some bacterial infections such as Streptococcal Sore Throat, Pneumonia and Acute Ear Infection are also more common in winter season.  As the environment cools, our body temperature usually experiences a drop; at the same time, the body is adjusting to the new climate through different processes. As a result, the change in the process results in a number of diseases e.g. heart attack.Most of us are unaware of the fact that winter is one of the prime seasons for heart attacks. As the temperature falls, the arteries become constricted making it difficult for the heart to pump the blood [2]. The heart also has to work harder to maintain body temperature when it's cold.Pain and stiffness of joints and muscles are common in during winter season; although there is no scientific evidence to these. It is most commonly seen in arthritis patients making their life miserable.Some minor ailments such as dry skin, itchy skin, chapped lips and cracked heels are universal in winter season.There are a strong relation between weather and mind. A number of people feel stressed in winter and some other are depressed. This is called Seasonal Affective Disorder (SAD) and it can lead to a lot of health issues related to these.Some precautions can prevent or at least reduce the incidence and suffering of people.
Keywords: Winter Illness; Editorial